Synthesis and characterization of a new 4-methoxysalicyliden-p-aminoacetophenoneoxime and its complexes with Co(II), Cu(II) and Zn(II) - Tuna, S.; Canpolat, E.; Kaya, M. (Polish Chemical Soc, 2006)
The novel Schiff base ligand, 4-methoxysalicyliden-p-aminoacetophenoneoxime (LH) was synthesized starting from p-aminoacetophenoneoxime and 4-methoxysalicylaldehyde. Mononuclear cobalt(II), copper(II) and zinc(II) complexes of the ligand have been prepared by using Co(II), Cu(II) and Zn(II) salt with a metal to ligand ratio of 1:2. The structures of the ligand and its complexes were identified by using elemental analyses, IR, H-1- and C-13-NMR spectra, magnetic susceptibility measurements, UV spectra and thermogravimetric analyses (TGA).
Keywords: Schiff bases; cobalt(II); copper(II) and zinc(II) complexes of Schiff bases